Allelic polymorphism of glucocorticoid receptor NR3C1 (GR): from molecular biology to clinical implications - Orlovsky, M.A. (Вiopolymers and Cell, 2012)
Polymorphism of stress-related genes is a key factor determining difference in the stress reactivity and resistance among humans. Glucocorticoid receptors are important actors of stress responses. This review is focused on the molecular biology and clinical implications of glucocorticoid receptor gene polymorphism. Keywords: glucocorticoid receptors, allelic polymorphism, SNP, NR3C1, GR, stress-induced pathology.